Loss of expression and nuclear/cytoplasmic localization of the FOXP1 forkhead transcription factor are common events in early endometrial cancer: relationship with estrogen receptors and HIF-1alpha expression. - Giatromanolaki, A; Koukourakis, M; Sivridis, E; Gatter, K; Harris, A; Banham, A (2006)
The FOXP1 gene has been identified as a new member of the winged helix family of transcription factors that have important roles in cellular transformation, differentiation and proliferation. In this study, we examined the expression of FOXP1 in the normal and malignant endometrium (stage I endometrioid adenocarcinoma cases), showing a frequent deregulation of its expression in cancer. Proliferative endometrium showed predominantly nuclear localization of FOXP1, while exclusively weak cytoplasmic staining was present in the secretory phase. Loss of nuclear expression was the most striking event in endometrial adenocarcinoma. Nuclear expression ranged from 0 to 20% (median 0%). Cytoplasmic expression was noted more frequently, ranging from 0 to 90% of cancer cells (median 30%). Overall, 24/82 cases (29.3%) were observed to lack both nuclear and cytoplasmic FOXP1 expression. Tumors with exclusively cytoplasmic expression of FOXP1 were linked with deep myometrial invasion and hypoxia-inducible factors 1alpha (HIF-1alpha) expression. On the other hand, the presence of nuclear FOXP1 expression was significantly linked with ER-alpha reactivity. Survival analysis did not reveal significant differences among patients grouped by FOXP1 expression, presumably due to the high curability of stage I disease. This study provides evidence on pathways to be investigated to elucidate the interplay between FOXP1, ER-alpha and HIF-1alpha in hormone dependent cancers.